Economic Analysis of Prevailing Agroforestry Systems Among Different Categories of Farmers In Kangra Valley of Himachal Pradesh, India - N. S, Kaler; K. S, Pant; B, Gupta; R, Bishisht; V., Attri; Vipasha (International Journal of Bio-resource and Stress Management, 2017)
The present study was conducted to evaluate the existing agroforestry systems and economic returns from the systems in Kangra district of Himachal Pradesh, India during the year 2014-15. A total number of 220 farmers were selected randomly from four group’s viz., marginal, small, medium and large based on landholding capacity for survey and data collection. The data was collected through pre-tested schedule for the purpose through personal interviews with head of the each household and field sampling. The study revealed that three agroforestry systems types prevalent among different categories of farmers namely: Agri-silviculture (AS), Agri-silvi-horticulture (ASH), Agri-horticulture (AH). The bio economics of the different systems were analyzed by calculating the cost of cultivation, gross returns ha-1, net returns per hectare and benefit:cost ratio. The higher net returns of agroforestry systems among different farmers category was observed maximum in Agri-silviculture (AS), large farmer’s category (` 240734.32) and benefit:cost ratio of agroforestry systems among farmers category was observed maximum in Agri-silvi-horticulture (ASH), large farmer’s category (2.00). Hence the study represents the clear picture of economic analysis of existing agroforestry system which will help the local peoples to fulfil their basic needs and the researchers to gain the benefit from the agroforestry.